Kandungan Nilai Pendikan Karakter Pendidik dalam Kitab Ta’līmul Muta’allim dan Relevansinya dengan Pendidikan Agama Islam - Raudhatinur, Raudhatinur (Al Mabhats : Jurnal Penelitian Sosial Agama, 2019)
Education is an effort made to acquire knowledge. To obtain this knowledge, there is a process called learning. Because learning is a process, several things in it that support the process to reap good results. Among the things that support the success of the learning process are characters. The method used in the discussion of this article is a descriptive method that is supported by data obtained through library research. By using library research, can examine, study, and study a variety of literature that is closely related to the problem discussed. The results of this study indicate: 1) the values of the character education of educators in Ta'līmul Muta'allim include the values of fatherhood, dignity, gentleness, gentle son. 2) the relevance of the values of character education contained in the book Ta'līmul Muta'allim have identical relevance, character education and Islamic education are one part. The values of character education contained in the book Ta'līmul Muta'allim are very suitable when implemented in the world of formal education in Indonesia because they will form a virtuous national character.